Concrete Concept of Business English - Tu, Long; Yan, Zeran; Liu, Huayan (Journal of Theory and Practice of Social Science, 2023)
Usually, business English mainly refers to the product of the combination of business and English. This subject includes the language application knowledge in all the aspect of business world in order to make sure the smooth going of all parts of business operation. Not only English language knowledge is needed, but also all the knowledge and abilities related to the business. The establishment of this risk assessment system solves the previous risk assessment of enterprises by Banks, which is mainly based on qualitative analysis and less on quantitative analysis, thus leading to the insufficiency of its relatively one-sided judgment standard. From the comprehensive strength and credibility of the two aspects of the study, extract five risk indicators to establish a risk assessment system. Among them, total input price and tax, total output price and tax, and profit rate are the evaluation criteria for the comprehensive strength of an enterprise. These indicators can analyze the production, sales and operation capacity, profitability and production and operation stability of an enterprise to reflect the comprehensive strength of the enterprise. The failure rate of the input transaction and the failure rate of the sales transaction are the evaluation standards of the enterprise's reputation. Such indexes can analyze the production management aspects such as the purchase planning of the enterprise's goods and the production quality management, to reflect the credibility of the enterprise. Therefore, the selection of these two aspects for analysis can fully evaluate the enterprise's credit risk.